2016
DOI: 10.1213/ane.0000000000001378
|View full text |Cite
|
Sign up to set email alerts
|

Arginase Inhibition Reverses Endothelial Dysfunction, Pulmonary Hypertension, and Vascular Stiffness in Transgenic Sickle Cell Mice

Abstract: Background In sickle cell disease (SCD), hemolysis results in the release and activation of arginase, an enzyme that reciprocally regulates nitric oxide (NO) synthase activity and thus, NO production. However, simply supplementing the common substrate L-arginine fails to improve NO bioavailability. In this study, we tested the hypothesis that arginase inhibition would improve NO bioavailability and thereby attenuate systemic and pulmonary vascular endothelial dysfunction in transgenic mice with SCD. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 31 publications
1
28
0
1
Order By: Relevance
“…Very recently, an oral arginase inhibitor has been developed for human use with anticipated phase 1 clinical trials for solid tumors recruiting soon. The potential benefits of arginase inhibitors for arginine deficiency syndromes remain to be determined, but a promising recent study demonstrated that arginase inhibition improved NO bioavailability and attenuated systemic and pulmonary vascular endothelial dysfunction in transgenic mice with SCD 159 . Therefore, arginase represents a potential therapeutic target in the treatment of cardiovascular dysfunction in hemolytic anemias.…”
Section: Methods Of Providing Conditionally Essential Amino Acidsmentioning
confidence: 99%
“…Very recently, an oral arginase inhibitor has been developed for human use with anticipated phase 1 clinical trials for solid tumors recruiting soon. The potential benefits of arginase inhibitors for arginine deficiency syndromes remain to be determined, but a promising recent study demonstrated that arginase inhibition improved NO bioavailability and attenuated systemic and pulmonary vascular endothelial dysfunction in transgenic mice with SCD 159 . Therefore, arginase represents a potential therapeutic target in the treatment of cardiovascular dysfunction in hemolytic anemias.…”
Section: Methods Of Providing Conditionally Essential Amino Acidsmentioning
confidence: 99%
“…; Steppan et al. ). We have previously shown that NOS and arginase compete for their common substrate, l ‐arginine, such that greater expression and/or activity of one results in lower activity of the other due to limitations in l ‐arginine bioavailability (Nelin et al.…”
Section: Introductionmentioning
confidence: 98%
“…I read with interest “Arginase Inhibition Reverses Endothelial Dysfunction, Pulmonary Hypertension, and Vascular Stiffness in Transgenic Sickle Cell Mice” 1 . Alterations in the arginine metabolome have been extensively studied in sickle cell disease (SCD), in humans as well as in SCD-transgenic mice 2 .…”
mentioning
confidence: 99%
“…Alterations in the arginine metabolome have been extensively studied in sickle cell disease (SCD), in humans as well as in SCD-transgenic mice 2 . Although Steppan and colleagues suggest that supplementing L-arginine does not improve nitric oxide (NO) bioavailability 1 , a more comprehensive review of the literature suggests benefits resulting from L-arginine therapy that are likely NO-related 2 . Pulmonary hypertension (PH), leg ulcers and vaso-occlusive pain are SCD-clinical subphenotypes of arginine deficiency that are reversed with arginine supplementation 2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation